Does God Matter? Religious Content and the Evaluation of Comforting Messages in the Context of Bereavement - Wilkum, Kristi and MacGeorge, Erina L. (Communication Research, 2010)
Many people use religious belief and practice as a resource for coping with distress. However, the influence of religious content in comforting messages has yet to be examined. The current study was designed to examine how comforting messages that vary in person centeredness and incorporate different kinds of religious content are evaluated by people who vary in intrinsic religiosity and styles of religious coping. College students ( N = 312) were asked to imagine that a grandparent had died and to evaluate the perceived quality of comforting messages representing different levels of person centeredness and types of religious content. They also completed measures of intrinsic religiosity and religious coping style. Results indicate not only a preference for messages with deferring religious content (in which God is described as responsible for helping the individual cope with the loss) but also variation in evaluation as a function of intrinsic religiosity and religious coping style.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjA5MzU2NDM4